Determinants of Murabahah Financing at Indonesian Sharia Banks - Mardianto, Dedi; Putri, Afriliya Tri (PT. Riset Press International, 2025)
This research aims to analyze murabahah financing based on the influence of inflation, interest rates, and third-party funds on BSI. The data used is secondary data on Murabahah Financing, deposits, inflation, and interest for February 2021 to February 2024, sourced from the official websites of BSI and BI. The method used is a quantitative method with multiple regression analysis. The results of the study obtained from multiple regression analysis show that the variables of deposits, inflation, and interest rates have a significant positive effect on murabahah financing at BSI in 2021-2024. Likewise, deposits, interest, and inflation significantly influenced murabahah financing at BSI in 2021-2024. The results of this study imply that banks need to pay attention to these macroeconomic factors in formulating business strategies and murabahah financing products, as well as increasing deposits by offering products and services that are attractive to customers. In addition, Sharia bank also needs to monitor the development of interest rates and inflation to be able to adjust the strategy to be carried out with various dynamic macroeconomic conditions.